Pleurapunktion – Schritt für Schritt - Leo, Fabian; Makowska, Magdalena (DMW - Deutsche Medizinische Wochenschrift, 2018)
Pleural effusions of unknown origin and parapneumonic effusions almost invariably require thoracentesis. Fluid analysis is fundamental and guides further diagnostic and therapeutic decisions. Thoracentesis yields high diagnostic value and is a generally safe procedure – given that some basic principles are considered.
Keywords: Pleurapunktion; Thorakozentese; Pleuraerguss; Parapneumonischer Erguss